2016
DOI: 10.4172/2329-6836.1000211
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Organo-Sulphur Volatiles in Allium sativum by Factorial Design

Abstract: The influence of temperature and time of heating on the production and composition of organosulfur compounds (OSC) in Allium sativum were investigated in a two-level design with two factors. The organosulfur compounds were identified by Headspace-GC-MS. It was established that temperature plays an important role in the regulation of the production of monosulfides and trisulfides. The effect of both negative and positive temperatures on the production and decomposition of OSC were showed. Although, monosulfides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Allylsulfides have shown a hepatoprotective effect and improve liver damage. Research has confirmed that diallyl disulfide increases the activity of antioxidant enzymes and reduces lipid peroxidation [79]. Allicin has antimicrobial, anti-inflammatory, antithrombotic, and anticancer properties [46].…”
Section: Health Benefits Of Garlicmentioning
confidence: 99%
“…Allylsulfides have shown a hepatoprotective effect and improve liver damage. Research has confirmed that diallyl disulfide increases the activity of antioxidant enzymes and reduces lipid peroxidation [79]. Allicin has antimicrobial, anti-inflammatory, antithrombotic, and anticancer properties [46].…”
Section: Health Benefits Of Garlicmentioning
confidence: 99%
“…Nitra Khodadadi et al (2015) in their experiment confirmed the site´s impact on the content of sulphur compounds and also on the total polyphenols content and the value of antioxidant activity. Chekki et al (2016) reported that the content of bioactive compounds is affected by the climatic conditions of the area. Sárosi et al (2011) reported that the content of bioactive constituents in plants is heavily influenced by climatic conditions.…”
Section: Bardejovmentioning
confidence: 99%
“…phaseoli and Penicillium digitatum (Obagwu & Korsten, 2003). Antimicrobial activity of garlic is apparently due to the high content of organosulfur compounds (Khadri et al, 2011;Ankri & Mirelman, 1999) such as allycin or diallyl thiosulfinate (Block, 2010), allyl ethyl trisulfides, dithiins, ajoen, diallyl sulfides, diallyl disulfides, allyl propyl disulfides, diallyl trisulfides, and diallyl tetrasulfides (Amagase, 2006;Chekki et al, 2016). The purpose of this study was to determine the fungicidal activity of some garlic extracts on plant pathogenic fungi such as C. capsici, F. capsici, and S. rolfsii.…”
Section: Introductionmentioning
confidence: 99%